2010
DOI: 10.1111/j.1365-2036.2010.04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated diverticular disease is not a common cause of colonic symptoms

Abstract: SUMMARY BackgroundColonic diverticular disease is common among older individuals whereas colonic symptoms, such as those of irritable bowel syndrome, are frequent in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…conducted a population‐based study of 2267 questionnaire respondents, showing that both functional constipation and constipation‐predominant IBS were not associated with diverticulosis . Several prior studies and our own findings have suggested that constipation is not positively associated with diverticulosis …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…conducted a population‐based study of 2267 questionnaire respondents, showing that both functional constipation and constipation‐predominant IBS were not associated with diverticulosis . Several prior studies and our own findings have suggested that constipation is not positively associated with diverticulosis …”
Section: Discussionmentioning
confidence: 68%
“…Another study from Kang et al . showed the frequency of constipation and constipation‐predominant IBS was similar in patients with and without diverticulosis . Jung et al .…”
Section: Discussionmentioning
confidence: 90%
“…An important subgroup amounting to around 20% of patients with diverticulosis suffer from recurrent short‐lived abdominal pain. Some authors have suggested that the occurrence of symptoms in patients without evidence of acute diverticulitis is incidental 35 . There is, however, a growing body of evidence which suggests that those patients with symptomatic disease have distinct abnormalities in motor function, inflammatory, neural, and psychologic changes that differ from asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that the occurrence of symptoms in patients without evidence of acute diverticulitis is incidental. 35 There is, however, a growing body of evidence which suggests that those patients with symptomatic disease have distinct abnormalities in motor function, inflammatory, neural, and psychologic changes that differ from asymptomatic patients. Previous theories of the etiol-ogy of symptoms in diverticular disease have focused on the role of structural and luminal changes in the condition, particularly, the role of high pressure colonic contractions.…”
Section: Previous Literaturementioning
confidence: 99%
“…42 The study used Rome criteria for IBS to classify patients and the response rates were high. Subjects completed questionnaires prior to structural exams.…”
Section: Chronic Symptomsmentioning
confidence: 99%